Design of multi-band passive RFID tag antenna - Yussuf, Abubeker A.; Islam, Md. Rafiqul; Alam, A. H. M. Zahirul; Khalifa, Othman Omran; Chebil, Jalel; Abdel Raouf, Hany Essam; Haji, Ibrahim A. (IEEE, 2010)
This paper presents the design of Multi-Band Passive RFID Tag Antenna with rectangular fractal shape and two operating bands for Radio Frequency Identification (RFID). The proposed antenna has wide and dual bandwidth verified by Simulated. It covers the wide frequency range including microwave bands of a 2.45GHz and 5.8GHz. This design of multiband antenna shows promising results at two different resonance frequencies with reasonable high return loss (S11) values and the highest possible antenna efficiency. The design challenge is getting this small size antenna for short distance applications that has good efficiency and radiation for both aforementioned frequency ranges. Several properties of the proposed antenna for multi-band operation have been investigated which include the return loss, radiation pattern and gain by using the commercial software CST.